An investigation into regional ventilation in infants and children; its distribution and determinants - Lupton-Smith, Alison Rosalie (Department of Paediatrics and Child Health, 2017)
Changing body position is commonly used in the management of individuals with respiratory diseases and those receiving mechanical ventilation, in order to optimise ventilation and oxygenation. In acute respiratory distress syndrome (ARDS), prone positioning is reported to improve oxygenation by recruiting collapsed dorsal lung regions, although this has not been confirmed in children. Ventilation distribution is well established in adults as being gravity dependent. Clinical practice in the paediatric population has been guided by the notion that all children, irrespective of the presence or absence of disease and age, consistently demonstrate the opposite ventilation distribution pattern to adults and this pattern is said to occur until the second decade of life. Studies in the paediatric population are limited to a few reported from the 1980's, on very heterogeneous populations. With advances in technology, new methods of examining regional ventilation, such as electrical impedance tomography (EIT), have become available. Recent neonatal studies using EIT have reported a dissimilar ventilation distribution to the conventional paediatric pattern. Despite a growing number of studies examining the effects of various interventions on ventilation distribution, very few exist in infants and children older than 6 months of age. Furthermore, differing methodologies and the manner in which ventilation distribution is described and analysed makes pooling the available data in the paediatric population extremely difficult. An understanding of how ventilation is distributed under normal conditions is imperative when examining the effects of different interventions and medical conditions on ventilation distribution. This thesis aimed to describe the effects of body position, head position, age, and respiratory muscle activity on ventilation distribution in children between six months and nine years of age under normal conditions, with respiratory disease, neuromuscular disease, and during mechanical ventilation. Furthermore, the effect on ventilation distribution of prone positioning in children with ARDS was evaluated. Regional ventilation distribution was measured using thoracic EIT and respiratory muscle activity was measured using surface electromyography (sEMG) using standardised methodology. Results of a series of sub-studies indicate that ventilation distribution is more complex and variable than previously thought, with no standard "paediatric pattern" of ventilation. Overall, greater ventilation occurred in the right and dorsal lungs, respectively, in different positons. Head position did not affect regional ventilation in the children studied. Age had a variable effect on ventilation distribution, with healthy children under 12 months of age more likely to follow the paediatric pattern, particularly in side lying positions; however the response was not uniform. The presence of mechanical ventilation, disease state and respiratory muscle activity did not affect ventilation distribution with these children also showing variable patterns of regional ventilation distribution. Data suggests that turning children with ARDS into the prone position does not result in recruitment of the dorsal lung regions, but rather more homogenous ventilation throughout the lungs. Furthermore, results suggest that children with greater ventilation inhomogeneity at baseline are more likely to respond positively (improvement in oxygenation index) to prone positioning. This research provides novel insights into ventilation distribution and respiratory muscle activity in infants and children older than six months of age under a number of different conditions. These results contribute to a better understanding of the factors influencing the distribution of regional ventilation and the mechanisms by which prone positioning in ARDS may improve oxygenation in this population. These findings have potentially important clinical implications, as well as providing baseline data for future clinical studies. Given the variability observed, these studies highlight the potential clinical utility of EIT to monitor different interventions and outcomes. An important strength of the studies presented in this thesis, is that they were performed in a standardised manner, using relatively homogenous individual populations and validated measures of describing ventilation distribution. This methodology could provide a template for future studies in the paediatric population, to allow for comparison between studies.